Green fabrication of biodegradable cork membrane for switchable separation of oil/water mixtures. Issue 2 (15th January 2021) - Zhou, Yanbiao; Qu, Kaige; Zhang, Lihui; Luo, Xiaoqiang; Liao, Binghua
Abstract: Cork is a renewable and biodegradable raw material, which was directly stripped from the periderm of oak bark. The natural amphiphilic chemical composition endowed its pristine surface with hydrophobicity and superoleophilicity in air. Based on the wettability of pristine cork, a stable superhydrophilic and superoleophilic cork membrane without any coating was fabricated via a facile, low-cost, and eco-friendly ethanol- and H2 O2 -treating process. The superamphiphilic treated membrane exhibited underwater superoleophobicity or underoil superhydrophobicity just by prewetting it with water or oil. This superamphiphilicity of the obtained membrane, combined with its natural permeability of tracheids, plasmodesmata and capillaries, enabled it to separate heavy oil from water or separate water from light oil. Furthermore, without using any continuous external stimulus, a good reversible switching between underwater superoleophobicity and underoil superhydrophobicity could be achieved simply by drying and washing alternately. With such superwettability, the membrane could selectively separate oil/water mixtures with high separation efficiency over multiple cycles solely driven by gravity. Moreover, the membrane could maintain superamphiphilicity in air and superamphiphobicity under liquids after scratching by a penknife or rubbing by a sandpaper. This simple but effective strategy will inspire the design and fabrication of other plant membranes for practical applications in oil/water separation. Graphical Abstract: uf0001